2023
DOI: 10.1200/jco.2023.41.16_suppl.1554
|View full text |Cite
|
Sign up to set email alerts
|

Can synthetic data accurately mimic oncology clinical trials?

Abstract: 1554 Background: There is strong interest by researchers, the pharmaceutical industry, medical journal editors, funders of research, and regulators in sharing clinical trial data. Reusing data extracts the most utility possible from patient contributions. The majority of patients do want to share their data for secondary research purposes. However, data access for secondary analysis remains a challenge. A key reason why individual-level data is not made directly available to data users by authors and data cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To address these challenges, the exploration of methods for generating synthetic data is underway. [13][14][15][16] The Bayesian network (BN) is a graphical structure that represents the conditional probability of nodes, where the nodes represent continuous or discrete nodes. 17 Studies have demonstrated that a BN can effectively capture variable correlations and generate synthetic data resembling the original data set.…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, the exploration of methods for generating synthetic data is underway. [13][14][15][16] The Bayesian network (BN) is a graphical structure that represents the conditional probability of nodes, where the nodes represent continuous or discrete nodes. 17 Studies have demonstrated that a BN can effectively capture variable correlations and generate synthetic data resembling the original data set.…”
Section: Introductionmentioning
confidence: 99%